The dynamic experience of pain in burn patients: A phenomenological study - Pérez Boluda, María Teresa; Morales-Asencio, José Miguel; Carrera Vela, Alejandro; García-Mayor, Silvia; León-Campos, Álvaro; López-Leiva, María Inmaculada; Rengel-Díaz, Cristóbal; Kaknani-Uttumchandani, Shakira (Elsevier, 2016)
Although pain is one of the main sources of suffering during the acute phase and rehabilitation in burn patients, it remains as a major challenge for burn care, and clinical management not always correlates with the experience felt by patients. The aim of this study was to understand the experience of pain from people who has suffered severe burns, to identify personal strategies used to cope with this challenging event. A qualitative phenomenological study with purposive sampling was carried out with severe burn patients admitted to a Burn Unit. Through individual in-depth interviews, verbatim transcription and content analysis, two main categories were isolated: a dynamic and changing experience of pain, from the onset to the hospital discharge, and diverse strategies developed by patients to cope with pain, being distraction the most frequently used. Pain experienced acquires its maximum intensity during wound care, and divergent patients’ opinions about sedation are present. This study highlights how understanding subjective experiences is an invaluable aid to improve care in pain assessment and management. Furthermore, it points out the need to guarantee patient involvement in the organization and improvement of burn care, inasmuch as traditional professional centered approach is not ensuring an optimal management.
Keywords: Quemaduras; Burns; Qualitative research; Coping; Pain